Urban mega projects on the rise: spatial and temporal shifts in urban development (1976–2020) - Cohen, Bilha; Cohen, Nir; Rotem-Mindali, Orit (Frontiers in Built Environment, 2026)
Research on urban mega-projects (UMPs) has primarily focused on their characteristics, stakeholder dynamics, and social and environmental implications, often using qualitative descriptions, while their spatial and temporal patterns remained underexplored. This study aims to address these gaps by defining distinct types of UMPs and establishing threshold values for each; presenting an urban-intensity index developed to highlight the role of market-driven, neoliberal urban development approaches in shaping the nature, location, and impact of these projects on the urban environment; and analyzing UMPs’ temporal and spatial distribution patterns across the Tel Aviv metropolitan area. A unique database of all UMPs constructed between 1976 and 2020 in that area was used in this examination. Through GIS mapping and analysis, the study investigates the development of these large-scale projects at macro (metropolitan) and micro (urban) levels. The findings reveal that while UMPs are not a new phenomenon, they have surged in prevalence over the past 2 decades, with 88% of projects completed since 2000, 77% of those since 2000 are classified as high-intensity. Spatially, 67% of UMPs are concentrated in Tel Aviv and adjacent cities, while 35.7% are located outside the metropolitan core, including 32% in neighboring cities. This study makes a threefold contribution: it introduces a quantitative, longitudinal approach to UMP research, establishes threshold values for smaller countries, and develops a novel index designed to assess the urban intensity of high-rise UMPs. Its extensive database and findings offer valuable insights for both stakeholders involved in UMP planning and development.